The Closed Proportional System in the Election of Legislative Members in Indonesia - Rauf, Dicky Andika (Universitas Negeri Gorontalo, 2024)
As a country with a representative democracy system, Indonesia regularly holds legislative elections. Since its independence, Indonesia has used two electoral systems: the closed proportional system and the open proportional system. In 2023, there was a debate about shifting from the open proportional system back to the closed proportional system. This issue is the focus of this study. Using normative research methods and qualitative analysis of literature, the author identified the reasons behind this shift. The main concern is the conflict with the constitution. Other weaknesses of the open proportional system include high costs, long execution times, money politics, and corruption risks. The closed proportional system is considered more efficient in terms of costs, time, competition quality, and candidate quality. However, its main issue is public distrust of political parties. Despite its benefits, the closed proportional system is not yet suitable for Indonesia's current situation.